Financial independency : the way to hybridity : the case of NGO MOVE - Marques, Catarina Rodrigues (2021)
The State, as a sovereign and self-regulating entity of a country, leaves to the charge of Non-Governmental Organizations (NGOs) and Social Movements the resolution or appeasement of problems that it cannot achieve. They do notorious work, essentially focusing on society. Still, they cannot always unfold between fundraising needs and their mission. Considering the economic and social importance of those organizations, the strengthening of their work is the key-word. Which kind of problems and difficulties they face? This teaching case focuses on the case of MOVE, a nonprofit organization operating in São Tomé, Timor and Azores. The goal of MOVE is to fight poverty through entrepreneurship (doing micro consulting to local projects and training communities to do business and generate alternative incomes. MOVE’s board members are looking for solutions for the financial difficulties they face. MOVE depend on philanthropy, funds and donations. This basis is unstable and sometimes causes pressure, affecting negatively the impact they aspire. This analysis will offer different point of views, allowing board members to state a direction for MOVEs financial sustainability. Furthermore, in a time where the boundaries between positive impact and generating income are in the same line, this thesis will enable a better understanding of ways to accomplish both.